OCCS: Enabling the Dynamic Discovery, Harvesting and Delivery of Educational Content from Open Corpus Sources - WADE, VINCENT PATRICK; LAWLESS, SEAMUS; LAWLESS, SEAMUS SEAN TOMAS; HEDERMAN, LUCY MARY (My University, 2008)
The World Wide Web (WWW) provides access to a vast array of educational content, a great deal of which is ideal for incorporation into eLearning experiences. However sourcing, harvesting and incorporating appropriate content has proven to be a complex and arduous task. This paper introduces a system that enables the discovery and classification of educational content from open corpus sources, such as the WWW, and facilitates the incorporation of such content into eLearning systems. The Open Corpus Content Service (OCCS) discovers, harvests and indexes content through the implementation of a focused web crawler, content classifier and indexer. This reduces the cognitive load placed on the educator by content authoring, allowing them to focus on the pedagogical design of eLearning offerings.
The 8th IEEE International Conference on Advanced Learning Technologies
PUBLISHED
Santander, Cantabria, Spain
Keywords: Computer Science